2017
DOI: 10.1016/j.dld.2017.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Usability of a home-based test for the measurement of fecal calprotectin in asymptomatic IBD patients

Abstract: The adherence to home-based measurement of FC was fair. Usability scores for the home-based test were high. There was a good correlation with the centrally measured FC by ELISA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…To the best of our knowledge, this is the first study comparing the performance of the IB Doc ® with immunoturbidimetry. In a recent study by Heida et al a similar correlation coefficient of 0.85 was found when comparing IB Doc ® and ELISA readings (BÜHLMANN fCAL ELISA, BÜHLMANN Laboratories AG), and in a study by Bello et al a correlation coefficient of 0.88 was found comparing IB Doc ® and ELISA readings (BÜHLMANN fCAL ® ELISA, BÜHLMANN Laboratories) [9] , [10] . The intermediate imprecision of IB Doc ® was substantially higher than the intermediate imprecision of BÜHLMANN fCal ® turbo in our study, especially at FC concentrations greater than 200 µg/g.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first study comparing the performance of the IB Doc ® with immunoturbidimetry. In a recent study by Heida et al a similar correlation coefficient of 0.85 was found when comparing IB Doc ® and ELISA readings (BÜHLMANN fCAL ELISA, BÜHLMANN Laboratories AG), and in a study by Bello et al a correlation coefficient of 0.88 was found comparing IB Doc ® and ELISA readings (BÜHLMANN fCAL ® ELISA, BÜHLMANN Laboratories) [9] , [10] . The intermediate imprecision of IB Doc ® was substantially higher than the intermediate imprecision of BÜHLMANN fCal ® turbo in our study, especially at FC concentrations greater than 200 µg/g.…”
Section: Discussionmentioning
confidence: 52%
“…A limitation to this finding though, was that the study participants were a priori interested in home testing [10] . Bello et al found that female sex and less severe disease was associated with higher usability of the IB Doc® , and that younger people especially thought they would use the tool in the future [9] . Elkjaer et al found that a web-guided “constant care” approach for UC patients – a web based program where patients are educated in UC, in recognizing relapse and in starting correct treatment guided by the e-health program and a web-doctor – increases patient's compliance, quality of life, empowerment to self-initiated treatment and reduces healthcare costs [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Calprotectin detected in the stool has a direct relationship to mucosal damage from IBD as a consequence of this neutrophil degranulation. This protein is detected in stool using enzyme-linked immunosorbent assays, and studies show that concentrations of calprotectin correlate with the degree of intestinal inflammation [18][19][20]. A positive correlation between CT and endoscopic findings of IBD with fecal calprotectin levels has been documented in the literature [21].…”
Section: Discussionmentioning
confidence: 98%
“…At this point, there are still very limited data on COVID-19 patients with IBD on biologics, and more research is needed. Preliminary data in the surveillance epidemiology of coronavirus (COVID- 19) are under research exclusion (SECURE-IBD) [12]. A worldwide database is promising.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, over 50% of IBDoc ® users still wanted to use it in the future and suggested its use to other people [ 27 ]. Another study by Bello et al enrolled 58 IBD patients (40 CD and 18 UC) showing an IBDoc ® adherence rate of approximately 47% over an eight-week follow-up period (five measurements were expected) [ 28 ]. A good correlation was found between IBDoc ® and ELISA test (intra-class correlation coefficient = 0.88) and the home test had high diagnostic accuracy in predicting a FC > 300 μg/g with the ELISA test (sensitivity: 89.8%, specificity: 95.5%, negative predictive value: 91.4%, and positive predictive value: 94.6%) [ 28 ].…”
Section: Introductionmentioning
confidence: 99%